Clinico-serologic co-relation in bi-directional ABO incompatible hemopoietic stem cell transplantation - Sabita Basu; Supriya Dhar; Deepak Mishra; Mammen Chandy (Asian Journal of Transfusion Science, 2015)
Background: The ABO blood group system is of prime significance in red cell transfusion and organ transplantation. However, ABO compatibility is not critical in allogenic hemopoietic stem cell transplantation (HSCT) and approximately 40-50% of hemopoietic stem cell transplants are ABO incompatible. This incompatibility may be major, minor or bi-directional. Though there are descriptions of transfusion practice and protocols in ABO incompatible HSCT, there are considerable variations and transfusion support in these patients can be very challenging. Aims: The immunohematologic observations in two cases of bi-directional ABO incompatible HSCT have been described, and clinico-serologic correlation has been attempted. Materials and Methods: In both cases, peripheral blood stem cell harvests were obtained using the Cobe spectra cell separator. Immunohematologic assessments in the donor and recipient were done as a part of pre HSCT evaluation. Both the standard tube technique and column agglutination method (Ortho Biovue Micro Bead System) was used. Antibody screen was done by column agglutination method using three cell panel (Surgiscreen cells). Isoagglutinin titration was done by the master dilution method and standard validated techniques were used. Results: The pattern of laboratory findings in the two cases was different and so were the clinical outcomes. Although there was early engraftment in the first case, the second case developed pure red cell aplasia and this was well-reflected in the immunohematologic assessments. Conclusion: Immunohematologic assessment correlated well with the clinical picture and could be used to predict clinical outcome and onset of complications in ABO incompatible HSCT.